An economic evaluation of a self-management programme of activity, coping and education for patients with chronic obstructive pulmonary disease. - Dritsaki, M; Johnson-Warrington, V; Mitchell, K; Singh, S; Rees, K (SAGE Publications, 2015)
The aim was to undertake a cost-utility analysis ofa Self-Management Programme of Activity, Coping and Education (SPACE)for Chronic Obstructive Pulmonary Disease (COPD). The analysis was conducted alongside a six-month randomised controlled trial in 30 primary care settings. The economic analysis used data from 184 patients with confirmed diagnosis of COPD, Forced Expiratory Volume in One second (FEV1)/forced vital capacity (FVC) ratio <0.7 and with grade 2-5 on the Medical Research Council dyspnoea scale. Participants received either a self-management programme consisting of an education manual (SPACEforCOPD) and consultation or usual care. Six-month costs were estimated from the National Health Service and Personal Social Services perspective and Quality-adjusted life years (QALYs)were calculated based on patient responses at baseline and six months. The mean difference in costs between usual care andSPACE FOR COPD programme was -£27.18 (95% CI; -£122.59 to £68.25) while mean difference in QALYs was -0.10 (95% CI; -0.17 to -0.02). The results suggest that the intervention is more costly and more effective than usual care. The probability of the intervention being cost-effective was 97% at a threshold of £20,000/QALY gained. We conclude that the SPACE FOR COPD programme is cost-effective compared to usual care.